The Vascular Flora of Tetraclinis Ecosystem in the Moroccan Central Plateau - Dallahi, Youssef; Chahhou, Driss; Aafi, Abderrahman; Fennane, Mohamed (European Scientific Journal, ESJ, 2017)
The main objective of this study is to quantify the floral richness and diversity of Tetraclinis ecosystem in the Moroccan Central Plateau. The approach was based on over 300 floristic surveys covering the different parts of the Moroccan Central Plateau forests. It also entails the analysis and processing of data from studies in the region. The results indicate that there are 233 taxa belonging to 56 families.